Young Muslim Clicktivism and Religious Local Tradition Discourse in Banten and Yogyakarta - Ade Fakih Kurniawan; Arif Rahman; Mukhsin Achmad; Fahmi Rizki Fahroji (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
This paper focuses on the discourse of local religious traditions and its implication for the shifting religious authority among young Muslims in Banten and Yogyakarta dealing with their activity in social media (clicktivism). The existence of freedom of opinion and expression since the fall of the New Order and the widespread use of new media has had a significant influence on youth’s Muslimness, including the local Islamic tradition issues. In collecting data, this study utilized visual ethnography, observation, interview, and focus group discussion. While analyzing the collected data, we use Talal Asad’s Discursive Tradition. The research finds that the dissemination of information through social media was able to have a significant influence on the change in religious practices, especially in dealing with local religious (Islamic) traditions. This change is inseparable from the dynamic process of the discursive tradition of young Muslims on social media. Another implication of the process is a shift in religious authority from personal to impersonal.